Analysis of the community composition and diversity of endophytes in extremely spicy industrial chili peppers from Tibet using high-throughput sequencing - Zhang, Junze; Yin, Yebing; Wang, Yanying; Luo, Sicen; Li, Yu; Zhao, Wenxiang; Cao, Pengxi; Liu, Yixuan; Ma, Hongmei (Frontiers in Microbiology, 2025)
Industrial chili peppers contain more than 100 times the capsaicin content of common chili peppers; these peppers are primarily used for industrial processing and capsaicin extraction. Chili peppers thrive in warm temperatures, require plenty of sunlight, and are drought-resistant; therefore, making the high-altitude climate of Tibet ideal for their cultivation. Endophytes are microorganisms that can inhabit healthy plants at various stages of their life cycle. Through long-term co-evolution, endophytes and host plants establish a mutually beneficial symbiotic relationship, which assists plants in secondary metabolite production. This study investigated the differences in endophyte community structure across various lines of industrial chili peppers. It also explored the relationship between capsaicinoids and endophyte community composition in high-altitude habitats of Tibet using high-throughput sequencing to obtain fundamental data on industrial chili pepper endophytes. The results showed that the diversity of endophyte communities was characterized by conservatism among groups and that the composition and community structure of endophyte communities were specific to different groups. Community composition analysis revealed that there were generally consistent dominant phyla of endophytic microorganisms in industrial chili peppers, although differences in their relative abundance percentage were observed. Bacterial community composition at the genus level was less affected by capsaicin concentration across different groups; however, the fungal community composition at the genus level was more responsive to capsaicinoid concentrations than that of bacteria. Bacterial communities from four different chili pepper varieties showed significant differences in the enrichment of genera. Fungi were differentially enriched in two groups: the td1 group with high capsaicin concentrations and the sylj group with low capsaicin concentrations. Among the four groups, endophytic bacteria exhibited the highest percentage of genes associated with unknown functions, while fungal trophic patterns had the most significant percentage of unknown trophic types. Overall, this study provides a valuable reference for the efficient cultivation and utilization of industrial chili peppers in Tibet.